Konsep Sumpah (Al-Yamin) Dan Perlaksanaannya Di Mahkamah Syariah Selangor, Wilayah Persekutuan Kuala Lumpur, Labuan Dan Putrajaya - Wan Abdul Fattah Wan Ismail; Zulkifli Hasan (Universiti Sains Islam Malaysia, 2024)
The research entitled "Concept of Al-yamin and Its Implementation in Syariah Court of Selangor and Wilayah Persekutuan (Kuala Lumpur, Labuan and Putrajaya)" is one of the efforts to compile a comperehensive data on al-yamin with an objective to improve the implementation of Islamic law of evidence in Malaysia. The aim of this research is to give a clear picture on the usage of alyamin at the Syariah Court specifically in Selangor and Wilayah Persekutuan theoretically and practically. The findings of the research might be made a reference to the legal practitioners in Malaysia as well as other Islamic countries and then it is hoped that the implementation of al-yamin can be standardized and straightly it will avoid any misunderstanding on its usage. The method employed in conducting this study will be library research and fieldwork research. Firstly, library research mostly concerns by referring contemporary and traditional textbook from various madhhab, reported cases, enactment, acts and etc. Secondly, fieldwork research refers to collection of primary data through interviewing judges, lawyers, court's officers and academician. This research concludes that there was no unified implementation of al-yamin in the Syariah Court especially in determining the party's rights to implement al-yamirz, taghliz al-yamin has not been implemented accordingly and there was also no standard guideline in determining which parties are muddai' and mudda'a alaih. This situation is happened due to the absence of one specific Rule or guideline that should be followed by the legal practitioners in the court's proceedings.